Colloquy with Emily Bell at Columbia University on digital platforms, journalism, and society. Issue 1 (2nd January 2020) - Gonçalves, Alexandre; Arasa, Daniel
Abstract: This interview with Professor Emily Bell encompasses a variety of topics centered on the relationship between digital platforms and journalism, religion, and society. Issues range from the alarming phenomenon of a growing share of the population who avoid news altogether to the resistance of internet companies to regulate speech. Professor Bell is not sparing with her criticism of digital behemoths, defending comprehensive regulation and greater transparency in their algorithms and data. She talks at length about the seismic consequences of the technological revolution for journalism and the challenges in finding a sustainable business model for the news media. When it comes to religion, she points out that churches have an ally in digital platforms, which can be used to disseminate their messages far and wide. Nevertheless, she warns against the risk of jeopardizing ethical principles when such an alliance lacks critical judgement. Professor Emily Bell is the director of the Tow Center for Digital Journalism at Columbia University and an expert on the interplay of communication and technology.